Place over traits? Purchasing edibles from medical marijuana dispensaries in Los Angeles, CA. (October 2017) - Kepple, Nancy Jo; Freisthler, Bridget
Abstract: Objectives: To examine discrete purchasing behaviors of marijuana-infused edibles from medical marijuana dispensaries with the aim to identify potential venue- and individual-level targets for prevention. Methods: Two-stage, venue-based sampling approach was used to randomly select patrons exiting 16 medical marijuana dispensaries in Los Angeles, California during Spring 2013. Hierarchical generalized linear modeling was used to examine the likelihood of purchasing edibles among 524 patrons reporting a discrete purchase regressed on characteristics of the sampled dispensaries and their patrons. Results: At a venue level, patrons were more likely to purchase edibles from dispensaries located within Census tracts with higher median incomes or in close proximity to a higher number of dispensaries. At an individual level, patrons who identified as Black or Hispanic were associated with a lower likelihood of purchasing edibles when compared to patrons who identified as other non-White, non-Hispanic race/ethnicity. Conclusions: Place-based policies focused on regulating edible sales through dispensaries may be fruitful in influencing access to edibles. Additionally, social marketing campaigns may benefit from targeting both locations where edible purchases are more likely and populations who are more likely to purchase edibles. Highlights: Purchasing edibles is positively related to place-specific variables, such as count of dispensaries within 0.5 km. Lower likelihood of purchasing edibles among Black or Hispanic patrons compared to other non-White, non-Hispanic patrons. Place-based policies focused on regulating edible sales through dispensaries may be fruitful in influencing access.